Virtually borderless? Cultural proximity and international collaboration of developers - Lena Abou El-Komboz; Moritz Goldbeck (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2024)
Are national borders an impediment to online collaboration in the knowledge economy? Unlike in goods trade, knowledge workers can collaborate fully virtually, such that border effects might be eliminated. Here we study collaboration patterns of some 144,000 European developers on the largest online code repository platform, GitHub. To assess the presence of border effects we deploy a gravity model that explains developers' inter-regional collaboration networks. We find a sizable border effect of -16.4%, which is, however, five to six times smaller than in trade. The border effect is entirely explained by cultural factors such as common language, shared interests, and historical ties. The international border effect in Europe is much larger than the state border effect in the US, where cross-border cultural differences are much less pronounced, further strengthening our conjecture that culture is a main driver of the border effect in virtual collaboration.
Keywords: F66; J61; O31; O33; O36; 330; digitization; software development; knowledge work; culture; language